Review of Nilodosis Kieffer (Diptera: Chironomidae: Chironominae), with description of a new species from South China - Tang, Hongqu; Cranston, Peter S. (Zootaxa, 2017)
The male, female and pupa of Nilodosis austrosinensis Tang & Cranston, sp. n., reared from 2 reservoirs of south China, are described. The male can be separated from congeners by the presence of few squamal setae, a relatively long spur on the mid– and hind legs, a characteristic superior volsella and distinctive pattern of all legs. The female can be separated by features of genitalia, namely the absence of a ventrolateral lobe and the dorsomesal lobe with the apex usually curved. The pupa is separable by a bare tergite VIII and by characteristic spinulation of the sternites. The generic diagnosis is emended and some problems alluded to. This is the first formal record of Nilodosis from the Oriental region, indeed the first outside the Afrotropical region.